Antibiotic use from conception to diagnosis of child leukaemia as compared to the background population: A nested case–control study. Issue 7 (19th March 2015) - Gradel, Kim Oren; Kærlev, Linda
<x xml:space="preserve">Abstract</x> Background The role of infection in the aetiology of childhood leukaemia is unknown. We used prescriptions of antibiotics from Danish pharmacies as a proxy measure for the occurrence of infections. Procedure We investigated the association between exposure to antibiotics, from conception to leukaemia diagnosis, and the risk of leukaemia. Incident cases of leukaemia among children in Denmark, 1995–2008, with mothers having their earliest conception date in 1995, were individually matched to population controls by age, sex and municipality. Conditional logistic regression analyses assessed antibiotic redemptions in different time periods from conception up to 6 months before the diagnoses of all leukaemia types, acute lymphoblastic leukaemia [ALL] and ALL in 2‐ to 5‐year‐old children, adjusting for several potential confounders. Results A total of 120/360 (33.3%) leukaemia mothers and 1, 081/3, 509 (30.8%) control mothers redeemed antibiotics during pregnancy (P = 0.32). For children, the equivalent numbers were 276 (76.7%) and 2, 665 (75.9%) (P = 0.76). Histograms of antibiotic redemptions showed no temporal differences between leukaemia mothers/children and controls, which was confirmed in adjusted regression analyses (OR [95% CI]: 1.02 [0.75–1.38]). Only antibiotics redeemed during the first year after birth differed from this (OR [95% CI] for ALL diagnosed in 2‐ to 5‐year‐old children: 0.46 [0.31–0.66]). Conclusions In this hypothesis generating study, the similar amount and pattern of antibiotic redemptions in children with and without leukaemia indicate that infections play a minor role in the aetiology of childhood leukaemia. However, less antibiotic redemptions during the first year of life conform to Greaves' 'delayed infection hypothesis'. Pediatr Blood Cancer 2015;62:1155–1161. © 2015 Wiley Periodicals, Inc.